Technology and Femininity in Marcel L'Herbier's L'Inhumaine. Issue 2 (May 2019) - Shingler, Katherine
Abstract : This article examines the intersection of technology and femininity in Marcel L'Herbier's 1924 silent film L'Inhumaine, focusing on the film's articulation of a figure of machine-woman who may be read as alternately inhuman and posthuman. The article draws on previous scholarship by Maureen Shanahan and others who have read the film through the lens of queer theory, but contends that any queer potentiality is effectively shut down at the end of the film. Offering a new reading of the mysterious machine that is used to reanimate and transform the heroine, I argue that the vision of a posthuman, technologically-mediated woman that emerges at the end of the film is far from emancipatory, and that despite its questioning of normative femininity, L'Inhumaine ultimately advances a conservative gender politics that chimes with a broad social and cultural retour à l'ordre in 1920s France.